Prediksi Jumlah Kasus Penyakit di Jawa Timur Memanfaatkan Metode Simple Moving Average - Darmawan, Shynta Ayu Dwi; Karmilasari, Karmilasari (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Based on a review of the East Java Provincial Health Profile book for 2017 to 2021, public health conditions over the past few years show considerable differences in disease cases across 38 cities or districts. Determining disease management priorities based on health profiles, as well as predicting future disease case trends, is a difficult task. Therefore, a prediction strategy that uses historical data to estimate the pattern of disease cases in each region from year to year is needed, as well as a web-based system to implement the prediction. The steps taken include a literature study, the creation of a prediction model using the Simple Moving Average approach, and the implementation of the system with a MySQL database, PHP backend, and Angular frontend. The results showed the success of the disease case trend prediction application using historical data for five periods. Functionality testing and browser compatibility show that the system runs as expected in various environments, while usability testing using the WebQual 4.0 technique produces an average score of 4.34 (excellent), which indicates that the system successfully meets user needs.